2013
DOI: 10.1111/jth.12239
|View full text |Cite
|
Sign up to set email alerts
|

The predictive ability of bleeding risk stratification models in very old patients on vitamin K antagonist treatment for venous thromboembolism: results of the prospective collaborative EPICA study

Abstract: The predictive ability of bleeding risk stratification models in very old patients on vitamin K antagonist treatment for venous thromboembolism: results of the prospective collaborative EPICA study. J Thromb Haemost 2013; 11: 1053-8. Summary. Background:The optimal duration of anticoagulant treatment after venous thromboembolism (VTE) should be evaluated in relation to bleeding risk. This assessment is particularly difficult with elderly patients, because of their increased risk of both recurrences and hemorrh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
37
0
5

Year Published

2014
2014
2022
2022

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 45 publications
(42 citation statements)
references
References 17 publications
0
37
0
5
Order By: Relevance
“…The HAS-BLED score was derived from 3978 patients in the Euro Heart Survey on atrial fibrillation and has repeatedly been shown to be predictive of bleeding in various conditions, even in patients who are not treated with any anticoagulant drugs (table 4) [44,[49][50][51]. The first study evaluating the HAS-BLED score in VTE patients was performed in 663 elderly patients, and reported a poor c-statistic of 0.55 [52]. A second study, performed in 515 patients with various indications for the use of VKAs, reported a c-statistic of 0.57 for the HAS-BLED score for the entire population of VKA-users, without reporting the area under the curve for the VTE population separately [43].…”
Section: Bleeding-prediction Scores Derived From Non-vte Patient Popumentioning
confidence: 99%
“…The HAS-BLED score was derived from 3978 patients in the Euro Heart Survey on atrial fibrillation and has repeatedly been shown to be predictive of bleeding in various conditions, even in patients who are not treated with any anticoagulant drugs (table 4) [44,[49][50][51]. The first study evaluating the HAS-BLED score in VTE patients was performed in 663 elderly patients, and reported a poor c-statistic of 0.55 [52]. A second study, performed in 515 patients with various indications for the use of VKAs, reported a c-statistic of 0.57 for the HAS-BLED score for the entire population of VKA-users, without reporting the area under the curve for the VTE population separately [43].…”
Section: Bleeding-prediction Scores Derived From Non-vte Patient Popumentioning
confidence: 99%
“…It is has been shown that this group of patients benefit from having aspirin in addition to their warfarin treatment, since it reduces the risk of systemic embolism or death [2].…”
Section: Disclosure Of Conflicts Of Interestmentioning
confidence: 99%
“…The predictive ability of bleeding risk stratification models in very old patients on vitamin K antagonist treatment for venous thromboembolism: results of the prospective collaborative EPICA study: reply We were pleased to read the letter from Gaboreau et al [1] related to our recent article [2]. In this article, in a population of elderly patients anticoagulated with warfarin for venous thromboembolism (VTE), we applied available bleeding scores to evaluate their predictive ability for bleeding risk.…”
mentioning
confidence: 99%
“…In the EPICA study OBRI index, HEMORR2HAGES, RIETE score, HASBLED, ATRIA, and the ACCP score have been compared in very old patients (aged ≥ 80 years) receiving VKA for secondary prevention of VTE. All of these risk stratifi cation models appeared to have a scant accuracy in the aged population [38].…”
Section: Individual Bleeding Risk During Anticoagulationmentioning
confidence: 99%